2019
DOI: 10.1097/ico.0000000000001994
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Segment Optical Coherence Tomography Images in Microsporidial Keratoconjunctivitis

Abstract: Purpose: To describe the findings of anterior segment optical coherence tomography (AS-OCT) in patients with microsporidial keratoconjunctivitis. Methods: The observational study included 13 eyes from 13 patients. Slit-lamp photography and AS-OCT were performed using the Swept source OCT before corneal scraping. All cases were positive for Gram-chromotrope (modified trichrome) staining for Microsporidia spp. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Some reports also showed similar epithelial hyperreflective lesions on AS-OCT in other corneal diseases, including Meesman corneal dystrophy and microcystic keratitis related to contact lens use. 26 , 29 , 30 Dembski et al 26 reported a case of bilateral acute microcystic epitheliopathy after daily soft contact lens wear, and proposed that the hyperreflective material in the corneal epithelium as well as the edema of some cells possibly represent the accumulation of apoptotic end products in the intercellular spaces of the corneal epithelium. Similarly, the hyperreflective lesions on AS-OCT might be consistent with the accumulation of pre-apoptotic cells or degenerated cells caused by internalization of belantamab mafodotin or deposited drug products itself.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports also showed similar epithelial hyperreflective lesions on AS-OCT in other corneal diseases, including Meesman corneal dystrophy and microcystic keratitis related to contact lens use. 26 , 29 , 30 Dembski et al 26 reported a case of bilateral acute microcystic epitheliopathy after daily soft contact lens wear, and proposed that the hyperreflective material in the corneal epithelium as well as the edema of some cells possibly represent the accumulation of apoptotic end products in the intercellular spaces of the corneal epithelium. Similarly, the hyperreflective lesions on AS-OCT might be consistent with the accumulation of pre-apoptotic cells or degenerated cells caused by internalization of belantamab mafodotin or deposited drug products itself.…”
Section: Discussionmentioning
confidence: 99%
“…A single prospective study found that all 13 patients with MKC exhibited hyperreflective dots limited to the epithelial layers of the cornea on AS-OCT. AS-OCT is especially useful for distinguishing MKC from viral keratoconjunctivitis, which is more likely to present with a smooth epithelial surface and hyperreflective lesions in the subepithelial layer that extend to the anterior stroma. The authors of this study concluded that although AS-OCT could not serve as the gold standard for diagnosis, it may guide treatment, especially in conditions in which corneal scraping is not otherwise possible [45].…”
Section: Polymerase Chain Reactionmentioning
confidence: 95%
“…Namely, the multifocal epitheliopathy seen in MKC may be confused for Thygeson's superficial punctate keratitis [44], Acanthamoeba keratitis [43], mycobacterial keratitis [21], or viral keratoconjunctivitis [40]; however, the multifocal, coarse, raised epithelial infiltrates seen in MKC are a key distinguishing feature from the above listed clinical entities. Furthermore, subepithelial lesions seen in MKC are larger than the nummular infiltrates present in viral keratoconjunctivitis [45]. In contrast to MKC, adenoviral keratoconjunctivitis is often characterized by an increased number of dendritic cells in the central cornea due to the activation of the innate immune system [46].…”
Section: Differential Diagnosismentioning
confidence: 99%
See 2 more Smart Citations